Psychological Status Among Anesthesiologists and Operating Room Nurses During the Outbreak Period of COVID-19 in Wuhan, China - Li, Xin-yi; Wang, Jin; Zhang, Rui-xian; Chen, Luhua; He, Colin K.; Wang, Cheng-yao; Ke, Jian-juan; Wang, Yan-lin; Zhang, Zong-ze; Song, Xue-min (Frontiers in Psychiatry, 2020)
BACKGROUND: Coronavirus Disease 2019 (COVID-19) caused by a novel strain of coronavirus (SARS-CoV-2) posed a major threat to public health. Anesthesiologists and operating room (OR) nurses are at high risk of occupational exposure to SARS-CoV-2 and developing COVID-19. We conducted a single-center survey to investigate the psychological status and perceived social support among operation room (OR) medical staffs during the outbreak of Coronavirus Disease 2019 (COVID-19). METHODS: A total of 197 OR medical staffs were enrolled in the survey. The authors performed a cohort study during the period of Wuhan lockdown and then conducted a longitudinal follow-up after lifting of lockdown. The Patient Health Questionaire-9 (PHQ-9) was used to assess for depression and Generalized Anxiety Disorder-7 (GAD-7) for anxiety. The Multidimensional Scale of Perceived Social Support (MSPSS) was used to assess perceived social support. We compared the psychological status of OR medical staffs before and after lifting of Wuhan lockdown. RESULTS: During the period of city lockdown, 177 (89.8%) had close contact with confirmed COVID-19 cases. The prevalence of depression and anxiety in OR medical staffs was 41.6% and 43.1% under Wuhan lockdown, while 13.2% and 15.7% after lifting of lockdown (P=0.002, P=0.004). Logistic regression analysis showed that being female, living in suburb areas, shortage of protective equipment and close contact with COVID-19 patients were associated with a higher risk of depression and anxiety. Perceived social support was negatively correlated with depression and anxiety severity in the OR medical staffs (P<0.05). CONCLUSIONS: OR medical staffs exhibited high incidence of anxiety and depression faced with the high risk of exposure to COVID-19 patients. More social support and social recognition for anesthesiologists and OR nurses might potentially help them relieve their psychological pressure.